Daily Fluctuation of Orexin Neuron Activity and Wiring: The Challenge of “Chronoconnectivity” - Azeez, Idris A.; Del Gallo, Federico; Cristino, Luigia; Bentivoglio, Marina (Frontiers in Pharmacology, 2018)
In the heterogeneous hub represented by the lateral hypothalamus, neurons containing the orexin/hypocretin peptides play a key role in vigilance state transitions and wakefulness stability, energy homeostasis, and other functions relevant for motivated behaviors. Orexin neurons, which project widely to the neuraxis, are innervated by multiple extra- and intra-hypothalamic sources. A key property of the adaptive capacity of orexin neurons is represented by daily variations of activity, which is highest in the period of the animal's activity and wakefulness. These sets of data are here reviewed. They concern the discharge profile during the sleep/wake cycle, spontaneous Fos induction, peptide synthesis and release reflected by immunostaining intensity and peptide levels in the cerebrospinal fluid as well as postsynaptic effects. At the synaptic level, adaptive capacity of orexin neurons subserved by remodeling of excitatory and inhibitory inputs has been shown in response to changes in the nutritional status and prolonged wakefulness. The present review wishes to highlight that synaptic plasticity in the wiring of orexin neurons also occurs in unperturbed conditions and could account for diurnal variations of orexin neuron activity. Data in zebrafish larvae have shown rhythmic changes in the density of inhibitory innervation of orexin dendrites in relation to vigilance states. Recent findings in mice have indicated a diurnal reorganization of the excitatory/inhibitory balance in the perisomatic innervation of orexin neurons. Taken together these sets of data point to "chronoconnectivity", i.e. a synaptic rearrangement of inputs to orexin neurons over the course of the day in relation to sleep and wake states. This opens questions on the underlying circadian and homeostatic regulation and on the involved players at synaptic level, which could implicate dual transmitters, cytoskeletal rearrangements, hormonal regulation, as well as surrounding glial cells and extracellular matrix. Furthermore, the question arises of a "chronoconnectivity" in the wiring of other neuronal cell groups of the sleep-wake-regulatory network, many of which are characterized by variations of their firing rate during vigilance states.